2021
DOI: 10.25259/ijdvl_338_20
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal amphotericin B is more effective in polymorphic lesions of post kala-azar dermal leishmaniasis

Abstract: Background: Post kala-azar dermal leishmaniasis (PKDL) is thought to be the reservoir of infection for visceral leishmaniasis in South Asia. The development of strategies for the diagnosis and treatment of PKDL are important for the implementation of the visceral leishmaniasis elimination program. Aims: Liposomal amphotericin B (L-AMB) has been an overwhelming success in the treatment of visceral leishmaniasis. However, the empirical three-week regimen of L-AMB proposed for PKDL was shown to be inadequate, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Miltefosine impacted substantially upon all antibody subclasses especially in the polymorphic form, and accounted for the decrease in IgG ( Fig 2Aii ) as also IgG1, IgG2 and IgG3 ( Fig 2D–2F ). This was in agreement with the parasite load wherein Miltefosine caused a dramatic decline in parasite load, more so in the polymorphic form [ 13 , 14 ]. Miltefosine mediates its leishmanicidal activity directly via parasite apoptosis [ 40 ] and indirectly by its immunomodulatory ability to skew macrophages towards a M2 phenotype, accompanied by a decrease in circulating levels of IL-10, TGF-β and IL-4 [ 24 ] which in this study translated into a decrease in the levels of Immunoglobulins ( Fig 3 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Miltefosine impacted substantially upon all antibody subclasses especially in the polymorphic form, and accounted for the decrease in IgG ( Fig 2Aii ) as also IgG1, IgG2 and IgG3 ( Fig 2D–2F ). This was in agreement with the parasite load wherein Miltefosine caused a dramatic decline in parasite load, more so in the polymorphic form [ 13 , 14 ]. Miltefosine mediates its leishmanicidal activity directly via parasite apoptosis [ 40 ] and indirectly by its immunomodulatory ability to skew macrophages towards a M2 phenotype, accompanied by a decrease in circulating levels of IL-10, TGF-β and IL-4 [ 24 ] which in this study translated into a decrease in the levels of Immunoglobulins ( Fig 3 ).…”
Section: Discussionsupporting
confidence: 83%
“…for 3 weeks [ 11 , 12 ]. The chemotherapeutic efficacy of Miltefosine vs. LAmB was assessed by quantifying the parasite load in skin biopsies [ 13 ] wherein irrespective of the lesional type, patients following treatment with Miltefosine showed an absence of parasite DNA that was sustained up to at least 6 months; however, with LAmB there was parasite persistence suggesting treatment inadequacy [ 13 , 14 ]. In resource limited settings, quantification of parasite load using nucleic acid based detection methods is not always feasible, endorsing the need to validate alternatives e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns were raised regarding the potential emergence of hypokalemia-induced rhabdomyolysis associated with its usage ( 44 ). The effectiveness of AmBisome in treating different types of lesions in Indian PKDL patients has been studied, and it has been observed that the response to treatment can vary depending on the lesion type ( 45 ). The study found that patients with polymorphic lesions showed a more pronounced decrease in parasite burden following treatment with AmBisome compared to patients with macular lesions.…”
Section: Treatment Options For Pkdlmentioning
confidence: 99%
“…9 While primary drug resistance is a growing concern, 10 host immune responses and the severity of clinical symptoms are also likely contributing factors to the variable treatment response. 7,11 Furthermore, severe pain at the injection site and the economic burden of reaching a secondary/tertiary hospital at regular intervals over several weeks affect treatment compliance. 12 Detailed observations of clinicopathology, along with the treatment response, may reveal correlations with the healing process in patients.…”
Section: Introductionmentioning
confidence: 99%
“…A patient's response to treatment and the time required for complete healing of the cutaneous lesion(s) depend on multiple factors 9 . While primary drug resistance is a growing concern, 10 host immune responses and the severity of clinical symptoms are also likely contributing factors to the variable treatment response 7,11 . Furthermore, severe pain at the injection site and the economic burden of reaching a secondary/tertiary hospital at regular intervals over several weeks affect treatment compliance 12 …”
Section: Introductionmentioning
confidence: 99%